Clinically SUspected ScaPhoid fracturE: treatment with supportive bandage or CasT? 'Study protocol of a multicenter randomized controlled trial' (SUSPECT study). Issue 9 (29th September 2020) - Cohen, Abigael; Reijman, Max; Kraan, Gerald A; Mathijssen, Nina M C; Koopmanschap, Marc A; Verhaar, Jan A N; Mol, Sander; Colaris, Joost W
Abstract : Introduction: Some scaphoid fractures become visible on radiographs weeks after a trauma which makes normal radiographs directly after trauma unreliable. Untreated scaphoid fractures can lead to scaphoid non-union progressing to osteoarthritis. Therefore, the general treatment for patients with a clinically suspected scaphoid fracture and normal initial radiographs is immobilisation with below-elbow cast for 2 weeks. However, most of these patients are treated unnecessarily because eventually less than 10% of them are diagnosed with an occult scaphoid fracture. To reduce overtreatment and costs as a result of unnecessary cast treatment in patients with a clinically suspected scaphoid fracture and normal initial radiographs, we designed a study to compare below-elbow cast treatment with supportive bandage treatment. We hypothesise that the functional outcome after 3 months is not inferior in patients treated with supportive bandage compared to patients treated with below-elbow cast, but with lower costs in the supportive bandage group. Methods and analysis: The SUSPECT study is an open-labelled multicentre randomised controlled trial with non-inferiority design. A total of 180 adult patients with a clinically suspected scaphoid fracture and normal initial radiographs are randomised between two groups: 3 days of supportive bandage or 2 weeks of below-elbow cast. We aim to evaluate the functional outcome and cost-effectiveness of both treatments. The primary outcome is the functional outcome after 3 months, assessed with the Quick Disability of the Arm, Shoulder and Hand score. Secondary outcomes include functional outcome, recovery of function, pain, patient satisfaction, quality of life and cost-effectiveness measured by medical consumption, absence from work or decreased productivity. Ethics and dissemination: The Medical Ethics Committee of the Erasmus MC Medical Centre, Rotterdam, approved the study protocol (MEC-2017-504). We plan to present the results after completion of the study at (inter)national conferences and publish in general peer-reviewed journals. Trial registration number: NL6976.